Haematology - Moore, Gary; Knight, Gavin; Blann, Andrew D. (Oxford ; New York : Oxford University Press, 2010)
Haematology provides a broad-ranging overview of the study of blood, the dynamic fluid that interfaces with all organs and tissues to mediate essential transport and regulatory functions. Written with the needs of the biomedical scientist centre-stage, it provides a firm grounding in the physiology of blood, and the key pathophysiological states that can arise. It demonstrates throughout how an understanding of the physiology underpins the key investigations carried out by a biomedical scientist to forge a clear link between science and practice. The Online Resource Centre to accompany Haematology features: For registered adopters of the book:Figures from the book, available to downloadFor students:An interactive Digital Microscope, encouraging the exploration of tissue samplesSelf-assessment modules to help you to check and reinforce understanding of the basic science introduced in each volumeVideo podcasts including interviews with practicing biomedical scientists, and 'in the lab' footage showing biomedical science in practice"--Provided by publisher.
Keywords: Hematology; Blood; Blood -- Pathophysiology; Blood Physiological Phenomena; Hematologic Diseases; Hematology -- methods